PENGARUH FAKTOR – FAKTOR PENENTU TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Risma Sekar Utami; Nugroho Heri Pramono (JURNAL ILMIAH EDUNOMIKA, 2024)
Profitability is one of the ratios that is very important for banks, because the profitability ratio is used as an indicator to measure the bank's efficiency in generating profits or profits by utilizing the assets owned by the bank. This research aims to determine empirically whether there is an influence between BOPO, NPF, Profit Sharing, NOM, Inflation and BI Rate on profitability as measured by Return On Assets (ROA) in Islamic Commercial Banks in Indonesia which are registered with the Financial Services Authority (OJK). The population in this study was 12 Islamic banks and the sample data obtained was 144 quarterly financial report data from Sharia Commercial Banks from 2020-2022 which was obtained from the official website of the Financial Services Authority. The analytical tool used is multiple linear regression analysis with data processing using SPSS version 26. The results of this research show that BOPO and NPF have a negative influence on the profitability of Sharia Banks. Meanwhile, NOM has a positive effect on the profitability of Sharia Banks. Apart from that, Profit Sharing, inflation and the BI Rate have no effect on the profitability of Sharia Banks.